OPTIMIZATION OF FOOD SAFETY CONTROL EFFORTS TO IMPROVE PUBLIC HEALTH STATUS - Anggraeni Endah Kusumaningrum (UNEJ e-Proceeding, 2017)
Food as a basic human need and fulfillment are part of human rights so that it isconstitutionally protected, which implies the emergence of state obligations toprovide safe food for its citizens. The complexity of the provision of safe food stilloccurs after the reformation, one of which is the field of food safety control on thecirculation of food that is not feasible. The method of research in this paper using thetype of normative legal research, with a juridical approach supported data types usedin this study are secondary data consisting of Primary Legal Material, Secondary LegalMaterial, and material of Tertiary Law. The results showed that the field of food safetycontrol is an important aspect in the provision of a safe food for the community. Thisshows that food safety issues for public health are still limited to procedural issuesand have not addressed substantial issues. Food safety can not be separated withgood food quality. Foods that meet safety standards and quality standards willcertainly improve the health status of the community, to achieve this, the food safetycontrol must be optimized.